2020
DOI: 10.1101/2020.09.30.294959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell analyses identify circulating anti-tumor CD8 T cells and markers for their enrichment

Abstract: The ability to monitor anti-tumor CD8+ T cell responses in the blood has tremendous therapeutic potential. Here, we used paired single-cell RNA sequencing and T cell receptor (TCR) sequencing to detect and characterize tumor matching (TM) CD8+ T cells in the blood of mice with MC38 tumors and melanoma patients using the TCR as a molecular barcode. TM cells showed increased activation compared to non-matching T cells in blood, and appeared less exhausted than matching counterparts in tumor. Importantly, PD-1, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 82 publications
5
14
0
Order By: Relevance
“…While we have further shown that it could be possible to enrich for circulating TILs by analyzing coexpression of genes encoding for surface markers, critical validation steps are required for implementation into a scalable immune-monitoring assay. Nevertheless, we note that in a companion paper by Pauken et al (2021) , circulating TILs could be identified by the expression of a set of gene markers partially overlapping with the ones that we found. The authors describe a combination of four negation markers ( CCR7 , FLT3LG , LTB , and GYPC ) that allows for enrichment of circulating TILs in treatment naive metastatic melanoma patients.…”
Section: Resultssupporting
confidence: 68%
“…While we have further shown that it could be possible to enrich for circulating TILs by analyzing coexpression of genes encoding for surface markers, critical validation steps are required for implementation into a scalable immune-monitoring assay. Nevertheless, we note that in a companion paper by Pauken et al (2021) , circulating TILs could be identified by the expression of a set of gene markers partially overlapping with the ones that we found. The authors describe a combination of four negation markers ( CCR7 , FLT3LG , LTB , and GYPC ) that allows for enrichment of circulating TILs in treatment naive metastatic melanoma patients.…”
Section: Resultssupporting
confidence: 68%
“…Therefore, the Simpson index of the clonal repertoire measured in the periphery may be a more accurate measure of the reservoir of clonally expanding, non-terminally exhausted T cells at the time of sampling. These findings are consistent with findings in the context of extracranial melanoma 74,75 . We validated this finding orthogonally on a patient-level basis by comparing phenotypic fraction with the Morisita Overlap Index (MOI, see Methods), a measure of TCR repertoire similarity between paired samples 76 .…”
Section: Intracranial T Cells Belonging To Clonotypes Detected In Blood Show Reduced Exhaustionsupporting
confidence: 91%
“…T cells, memory CD8 T cells, and IFN-responsive CD8 T cells were associated with non-clonally expanded T cells. These results are concordant with findings in both murine and clinical models of extracranial melanoma 74,75 , where there is an association between a T cell clone's phenotype and its shared presence in both the lesion and in the blood. This model of cross-talk between blood and extracranial tumors is similarly recapitulated within our cohort of melanoma brain metastases.…”
Section: While Exhausted and Cycling T Cell Clones Were Predominantly Expanded Cd4/foxp3supporting
confidence: 90%
“…In turn, this could lead to continued localized seeding of tumors with the generated effector T cells. Inflammatory signals produced by the activated T cells could also lead to further activation of neighboring myeloid and endothelial cells, promoting recruitment of additional resource and effector T cells from the vasculature, which has been observed after both checkpoint blockade and CEA-TCB therapies (Joyce and Fearon, 2015; Spitzer et al, 2017; Huang et al, 2018; Munn and Jain, 2019; Chow et al, 2019; Wu et al, 2020; Zhang et al, 2021; Cremasco et al, 2021; Pauken et al, 2021; Connolly et al, 2021). Additional chemoattraction and activation of T cells already present in the tumor is also likely (Chow et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 17, 2021. ; https://doi.org/10.1101/2021.06.17.448881 doi: bioRxiv preprint (Joyce and Fearon, 2015;Spitzer et al, 2017;Huang et al, 2018;Munn and Jain, 2019;Chow et al, 2019;Wu et al, 2020;Zhang et al, 2021;Cremasco et al, 2021;Pauken et al, 2021;Connolly et al, 2021). Additional chemoattraction and activation of T cells already present in the tumor is also likely (Chow et al, 2019).…”
Section: Discussionmentioning
confidence: 99%